2018
DOI: 10.1631/jzus.b1600490
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosome-associated microRNA in diagnostic and therapeutic applications to metabolic disorders

Abstract: Metabolic disorders are classified clinically as a complex and varied group of diseases including metabolic syndrome, obesity, and diabetes mellitus. Fat toxicity, chronic inflammation, and oxidative stress, which may change cellular functions, are considered to play an essential role in the pathogenetic progress of metabolic disorders. Recent studies have found that cells secrete nanoscale vesicles containing proteins, lipids, nucleic acids, and membrane receptors, which mediate signal transduction and materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 101 publications
0
30
0
Order By: Relevance
“…Exosomes are released by most of the cells into the circulation and bodily fluids display different protein and RNA contents in healthy subjects and patients with different diseases, which can be measured as potential diagnostic markers [ 198 , 199 ]. Several studies have examined circulating exosomes in human obesity and metabolic syndrome [ 200 , 201 , 202 , 203 ]. Obesity and other associated metabolic disorders induce increased secretion of vesicles incorporating specific RNAs and proteins as observed in both rodents and humans [ 204 , 205 ].…”
Section: Exosomes and Metabolic Dysfunctionmentioning
confidence: 99%
“…Exosomes are released by most of the cells into the circulation and bodily fluids display different protein and RNA contents in healthy subjects and patients with different diseases, which can be measured as potential diagnostic markers [ 198 , 199 ]. Several studies have examined circulating exosomes in human obesity and metabolic syndrome [ 200 , 201 , 202 , 203 ]. Obesity and other associated metabolic disorders induce increased secretion of vesicles incorporating specific RNAs and proteins as observed in both rodents and humans [ 204 , 205 ].…”
Section: Exosomes and Metabolic Dysfunctionmentioning
confidence: 99%
“…Thus, circulating miRNAs have been widely used as biomarkers in different types of human diseases such as liver diseases, tumors, diabetes, heart failure, coronary diseases and stable angina. [37][38][39][40] The current research on the relationship between microRNAs and pulmonary embolism had been performed Figure 2 Receiver-operating characteristic (ROC) curve analysis of serum miR-1233, miR-134, plasma D-dimer to discriminate AECOPD+APE patients from AECOPD controls. (A) The analysis showed that the receiver operating characteristic (ROC) area under the curve (AUC) for miR-1233 was 0.884 (95% CI 0.79-0.978)(P<0.05), the AUC for miR-134 was 0.931 (95% CI 0.863-0.999)(P<0.05); (B) the AUC for D-dimer was 0.628 (95% CI 0.447-0.809), the AUC for age-adjusted plasma D-dimer was 0.705 (95% CI 0.525-0.885), and the AUC for Wells score was 0.577 (95% CI 0.389-0.765).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, detection of exosomal protein; both CD9 and CD63 the well-known exosomal markers, and their expression were analyzed by Western blotting. Recent studies have detected more and more exosome associated miRNAs associated with different kinds of chronic diseases, especially metabolic disorders such as diabetes mellitus, fatty liver, obesity, and atherosclerosis [47].…”
Section: Discussionmentioning
confidence: 99%